Educational Videos on Local Wisdom “Topeng Dance and Basa Walikan” to Motivate the New Culture Clean and Healthy Living Behavior - Apryanto, Frengki; Zunaedi, Rosly; Ramadhani, Rahmaniah (Journal of Ners and Midwifery, 2025)
Environmental and behavioral factors influence health, so community empowerment is very important to achieve a healthy paradigm. The lack of clean and healthy living behavior in minimizing the risk of disease is due to lack of socialization, availability of facilities, and strong local culture. Further efforts are needed to achieve optimal results. The research aimed to determine the effectiveness of educational video local wisdom "Topeng Dance and Basa Walikan" on clean and healthy living behavior cultural motivation in preventing disease at the Mojolangu Malang Community Health Center. This was quantitative research with quasi-experimental design, pre-post test with control group design. Simple random sampling was used as the sampling technique. The population was 150 people who sought outpatient treatment at the Mojolangu Community Health Center. The get sample size software divides the sample into two groups; margin of error 5% for 110 samples. The intervention group was given five educational videos in stages over 15-30 minutes. The control group used the available brochures. The data collection used questionnaires. The data analysis used the Wilcoxon sign rank test and the Mann-Whitney test. The data analysis showed that the intervention affected the perceptions of vulnerability (p-value=0.000), Perception of Severity (p-value=0.000), Perception of Barriers (p-value=0.000), Perception of Benefits (p-value=0.000), cues to action (p-value=0.017), self-efficacy (p-value=0.000), and motivation (p-value=0.000). Meanwhile, in the control group there were no differences in pre-post-test. Health promotion needs to be increased to encourage sustainable healthy living behavior activities so that people can achieve the highest level of health.